Development of Powtoon Animation Learning Media on Flat Building Materials Class IV - Masito Wahyuni Hasibuan; Arrini Shabrina Anshor (PT Inovasi Pratama Internasional, 2023)
Research and development is a research method used to produce certain products and test the effectiveness of these products. Research and development or what is known as Research & Development (R&D) is product oriented in the field of education. This research was conducted at SD Negeri 105330 Bangun Sari, Tanjung Morawa sub-district, Deli Serdang Regency, in class IV students. The time for carrying out this research and development is in the even semester of the 2023/2024 school year. The subjects of this study were fourth grade students at SD Negeri 105330 Bangun Sari, totaling 37 students, consisting of 18 female students and 19 male students. This research was assisted by several mathematicians as a validator/assessment. The instruments used in this study were interviews, questionnaires and documentation. Material validation was carried out with the aim of obtaining material that was in accordance with the media being developed. The results of the material validation obtained an average value of 88% in the